Enhancing Students’ Engagement in English Language Learning Through Mentimeter: A Case Study - Rosmayanti, Vivit; Asrifan, Andi; Vargheese, K.J (JPTK : JURNAL PENELITIAN TINDAKAN KELAS, 2025)
This study examines Mentimeter’s effectiveness in increasing student participation in an English as a Foreign Language (EFL) classroom. Using a qualitative case study methodology, the research was carried out in a third-year English language course at Universitas Negeri Makassar, using class observations, students’ focus group interviews, and a questionnaire as data collection techniques. The study also seeks to understand the students’ engagement, such as behavioral, emotional, and cognitive engagement, in working with Mentimeter during the lesson. The results show that Mentimeter has been beneficial for all levels of engagement. For behavioral engagement, targets increased to 85% in participation rates and 92% in attendance as learning was focused on interactive and gamified sessions. Emotional engagement was improved as 78% of students who attended the sessions enjoyed it, while 81% of students agreed that such activities enhanced their interaction with studies rather than being boring. Respondents indicated deeper critical thinking affecting cognitive engagement with 45 new ideas created in brainstorming sessions, and of the 76% engaged, they felt that they understood and remembered the material better. This research study proves that the Mentimeter is an effective instrument in instructing English language learners that utilizes a more sustained and engaged participation, invoking desired emotions and thinking more. These results support the argument that factors such as the use of Mentimeter will improve students’ learning engagement in an EFL setting.